The double-mode nature of the HADS star GSC 00144-03031 and the Petersen diagram of the class - Poretti, E.; Suárez, J. C.; Niarchos, P. G.; Gazeas, K. D.; Manimanis, V. N.; van Cauteren, P.; Lampens, P.; Wils, P.; Alonso, R.; Amado, P. J.; Belmonte, J. A.; Butterworth, N. D.; et al. (2005)
The double-mode pulsation of GSC 00144-03031 has been detected when searching for COROT targets. A very large dataset composed of 4722 photometric measurements was collected at six observatories in Europe and America. There is no hint of the excitation of additional modes (down to 0.6 mmag) and therefore GSC 00144-03031 seems to be a pure double-mode pulsator, with a very short fundamental radial mode (P = 84 min). From uvbyβ photometry and evolutionary tracks it appears to be a Pop. I star with M = 1.75 M⊙, located in the middle of the instability strip, close to the Zero-Age Main Sequence. We also discovered other new double-mode pulsators in the databases of large-scale projects: OGLE BW2_V142, OGLE BW1_V207, ASAS3 094303-1707.3, ASAS3 000116-6037.0, NSVS 3234596 and NSVS 3324715. An observational Petersen diagram is presented and explained by means of new models. A common sequence connecting Pop. I stars from the shortest to the longest periods is proposed and the spreads in the period ratios are ascribed to different metallicities (at the shortest periods) and to different masses (at the longest ones).
Keywords: Astrophysics; methods: data analysis; stars: individual: GSC 00144-03031; Stars: oscillations; stars: variables: δ Sct; techniques: photometric